Strengthening Digital Literacy as a Strategy to Prevent the Commodification of Belis Culture in Manggarai - Femberianus Sunario Tanggur; Cahyo Budi Utomo; I G W Wisnuwardana; Saddam Saddam; Nuryanti Nuryanti (JURNAL PENDIDIKAN IPS, 2024)
The commodification of Belis culture in Manggarai, East Nusa Tenggara, Indonesia, is increasing, threatening the preservation of traditional values related to social honor and family relations. These values are now starting to shift into commodities that are traded for economic interests. Preservation efforts through education and cultural revitalization have not been effective in facing this challenge. Therefore, this study aims to examine the strengthening of digital literacy as a strategy to prevent the commodification of Belis culture. The research uses a qualitative approach with a case study method, which allows in-depth exploration of the phenomenon of cultural commodification. The results show that strengthening digital literacy is an important solution to protect Belis culture, by giving the community the ability to access and disseminate cultural information through digital platforms. Some of the strategies found in this research include: first, increasing the capacity of the community in utilizing digital technology to preserve Belis culture; second, creating educational content about Belis culture through articles, videos, and podcasts; and third, forming digital communities to support cultural preservation collaboratively.